Sexual Dimorphisms in Innate Immunity and Responses to Infection in Drosophila melanogaster - Belmonte, Rebecca L.; Corbally, Mary-Kate; Duneau, David F.; Regan, Jennifer C. (Frontiers in Immunology, 2020)
The sexes show profound differences in responses to infection and the development of autoimmunity. Dimorphisms in immune responses are ubiquitous across taxa, from arthropods to vertebrates. Drosophila melanogaster shows strong sex dimorphisms in immune system responses at baseline, upon pathogenic challenge, and over ageing. In this review, we synthesise evidence for sexually dimorphic responses to bacterial, viral, and fungal infections. Dimorphisms may be mediated by distinct immune compartments, and we review work on sex differences in behavioral, epithelial, cellular and systemic (fatbody-mediated) immunity. Emerging work on sexually dimorphic immune ageing and inflammation will be explored, with a focus on intestinal immunity and microbial dysbiosis. We consider evolutionary drivers for sex differences in immune investment, highlight the features of Drosophila biology that make it particularly amenable to studies of immune dimorphisms, and discuss areas for future exploration.